Novel Prognostic Factors Associated with Cell Cycle Control in Sporadic Medullary Thyroid Cancer Patients. (18th February 2019) - Pezzani, Raffaele; Bertazza, Loris; Cavedon, Elisabetta; Censi, Simona; Manso, Jacopo; Watutantrige-Fernando, Sara; Pennelli, Gianmaria; Galuppini, Francesca; Barollo, Susi; Mian, Caterina
Abstract : Background . Medullary thyroid cancer (MTC) is a rare neuroendocrine-derived malignancy. It is represented by sporadic and familiar forms, and both can have RET oncogene mutations. Numerous markers can be used to define MTC; however, none is generally approved for predicting the outcome of sporadic MTC. Aim . The aim of this work was to analyze PTTG1/securin and Aurora kinase A expressions in MTC patients, both at the gene and protein levels, and to define their prognostic role in MTC assessing their association with lab and clinical parameters. Patients and Methods . Seventy-one sporadic MTC human samples were analyzed for RET mutations and by qPCR for PTTG1 and AURKA (Aurora kinase A) expression. Ki-67 levels and western blot reactivity for PTTG1 and Aurora kinase A were also determined in a selected cohort of patients. Results . RET somatic mutations were found in 48% of the patients (34/71). PTTG1 expression was statistically different among the groups with or without regional lymph node metastasis (p < 0.0001 ) and advanced stage disease (p < 0.01 ). PTTG1 and AURKA expressions were statistically higher than those of controls (p = 0.01 andp < 0.002, respectively). PTTG1 expression and Ki-67 levels were statistically different among the groups with remitted or persistent disease (p < 0.05 andp < 0.01, respectively). We found a significant correlation between the expressions of AURKA and PTTG1 (p < 0.0002, r = 0.5298 ) and between the expressions of PTTG1 and Ki-67 (p = 0.01 ). Ki-67 levels were statistically different among the groups with or without metastatic lymph nodes (p = 0.01 ) or distant metastases (p = 0.003 ). Conclusion . The presence of an altered expression of PTTG1 and AURKA is a negative prognostic factor associated with a more aggressive course of disease, such as an advanced stage or disease persistence. It emerges as a cell cycle process mediated by the 2 factors, in addition to the RET pathway, which can be altered in MTC patients.